1999
DOI: 10.1007/pl00009620
|View full text |Cite
|
Sign up to set email alerts
|

Experience with percutaneous transhepatic cholangioscopy (PTCS) in the management of biliary tract disease

Abstract: PTCS is a safe, useful, and well-tolerated adjunct to the more common endoscopic and surgical techniques for managing complicated biliary tract disorders. Our experience suggests that PTCS can be performed early, without prolonged sequential dilatation of the percutaneous transhepatic tract, and may allow avoidance of operation in high-risk surgical candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…Nimura [10] reported that a PTCS-directed biopsy had a sensitivity of 96% for diagnosing cholangiocarcinoma. These results are significantly better than those reported for fluoroscopically guided biopsies [9]. In the present case, the lesion was too small to be detected on abdominal CT.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Nimura [10] reported that a PTCS-directed biopsy had a sensitivity of 96% for diagnosing cholangiocarcinoma. These results are significantly better than those reported for fluoroscopically guided biopsies [9]. In the present case, the lesion was too small to be detected on abdominal CT.…”
Section: Discussioncontrasting
confidence: 78%
“…Since first introduced by Takada et al in 1974 PTCS has been utilized to manage a variety of biliary tract disorders [9]. The introduction of small-caliber flexible cholangioscopes in 1976 by Yamakawa et al further enhanced the application of this technique [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Complications included trapped/broken basket, 9 traction wire fracture, 10 broken handle, 11 and perforation/duct injury. 12 The majority of complications related to intracorporeal lithotripsy were associated with (the process of) gaining pancreaticobiliary access (e.g., ERCP or percutaneous transhepatic access) and included pancreatitis, hemorrhage, perforation, and sepsis. Traditionally the treatment approach to these complications has been surgical.…”
Section: ) Intracorporeal Modalitiesmentioning
confidence: 99%
“…The cholangioscope's tip is lubricated and advanced into the biliary system through a 12F sheath placed through a preexisting mature (3-4 weeks) percutaneous tract. 49,50 After advancement to the duodenum or surgical anastomosis, the wire is removed for intraductal examination. The tract through which the sheath enters the liver predetermines the ducts that can be accessed with the cholangioscope; maneuvering to the opposite liver segment may be impossible through a single percutaneous tract.…”
Section: Percutaneous Cholangioscopymentioning
confidence: 99%